PENGARUH BUDAYA ORGANISASI, FASILITAS KERJA, DAN DISIPLIN KERJA TERHADAP KINERJA ASN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA KANTOR DPUPP KABUPATEN SITUBONDO - Akbar, Ach. Kiswandha Islamy; Praja, Yudha; Pramesthi, Riska Ayu (Fakultas Ekonomi dan Bisnis, 2024)
This aims of this research is to determine the influence of organizational culture, work facilities and work discipline on ASN performance through job satisfaction as an intervening variable at the Situbondo Regency DPUPP Office. This research used a quantitative approach which was carried out by distributing questionnaires to 59 ASN employees at the Situbondo Regency Public Works, Housing and Settlements Department. The method of data analysis used in this research is multiple linear regression analysis. The hypothesis test results have a direct effect using the Smart PLS 3.0 application. The results of direct hypothesis testing show that organizational culture has an insignificant effect on job satisfaction, work facilities have an insignificant effect on job satisfaction, work discipline has a significant effect on job satisfaction, organizational culture has an insignificant effect on ASN performance, work facilities have an insignificant effect on ASN performance, Work discipline has a significant effect on ASN performance. Job satisfaction has a significant effect on ASN performance. The results of indirect hypothesis testing show that the organizational culture variable has a negative but not significant effect on ASN performance through job satisfaction, work facilities have a negative but not significant effect on ASN performance through job satisfaction, and work discipline has a significant positive effect on ASN performance through job satisfaction.